Khāṇḍekara, caritra āṇi vāṅmaya - Deśapāṇḍe, Mādhava Kā. (Mādhava Kāśinātha) (SAMP early 20th-century Indian books project, 1941)
Study on the works of Vishṇu Sakhārāma Khāṇḍekara, 1898-1976, Marathi author.